Trading price action trading ranges technical analysis of price charts bar by bar for the serious trader - Brooks, Al, 1952- (Wiley trading., 2012)
"The introduction to this book will be short and related only to this volume. The market is either trending or in a trading range and it is often transitioning from one to the other. When the market is transitioning from a trading range into a trend, it is breaking out. Since trends were just discussed in the first book, this second book begins with how trading ranges turn into trends, which are now familiar to the reader. It explains why breakouts form and why they end, which is always at some kind of support or resistance area. The market gets drawn quickly to these areas and because of this pull, I refer to them as magnets. As the breakout is unfolding, traders can use several mathematical techniques to measure where the trend will likely end and then begin to form a trading range, and these measured moves are discussed in detail. Once the market reaches a magnet, it then pauses and pulls back, and usually then resumes. Pullbacks are reliable setups and the book describes them and how to trade them in detail. If a pullback grows so large that it is uncertain if the trend will resume or reverse, it has become a trading range. Most markets are in trading ranges most of the time and therefore most trades that traders make are within trading ranges. Understanding them and how to trade them is critical to anyone trying to make a living as a trader. Traders need to know how to place orders to get into and out of trades and it is useful to know how to scale into and out of positions. Also, mathematics is the basis for all trading. Every trader asks himself, "Will I make money if I take this trade?" This means that the traders is making a statistical analysis of what he sees based on risk, reward, and probability, and understanding this math makes trading less stressful and more profitable"--